2021
DOI: 10.1111/josh.13082
|View full text |Cite
|
Sign up to set email alerts
|

LGBTQ Student Health: A Mixed‐Methods Study of Unmet Needs in Massachusetts Schools

Abstract: BACKGROUND: Lesbian, gay, bisexual, transgender, and queer and questioning (LGBTQ) youth experience poor physical and mental health outcomes relative to their non-LGBTQ peers. School health professionals (SHPs), such as school nurses, play a key role in addressing LGBTQ student health needs. However, few studies examine school health needs of LGBTQ students from both the youth and SHP perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…These include victimisation, bullying, labelling as "stabane", funny looks, threats, insults, and teasing to belittle them on university premises (such as public spaces, bathrooms, and classrooms), which were based on their character. The findings are in line with Letsoalo [35], Sava, et al [36], Antebi-Gruszka, et al [37], and Treharne et al [38], which reported similar findings.…”
Section: Discussionsupporting
confidence: 88%
“…These include victimisation, bullying, labelling as "stabane", funny looks, threats, insults, and teasing to belittle them on university premises (such as public spaces, bathrooms, and classrooms), which were based on their character. The findings are in line with Letsoalo [35], Sava, et al [36], Antebi-Gruszka, et al [37], and Treharne et al [38], which reported similar findings.…”
Section: Discussionsupporting
confidence: 88%